2013
DOI: 10.1097/acm.0b013e31827c0d60
|View full text |Cite
|
Sign up to set email alerts
|

Deafness Among Physicians and Trainees

Abstract: DHoH physicians and trainees seemed satisfied with frequent, multimodal accommodations from employers and educators. These results may assist organizations in planning accommodation provisions. Because DHoH physicians and trainees seem interested in primary care and serving DHoH patients, recruiting and training DHoH physicians has implications for the care of this underserved population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…LGBTQ + -inclusive evidence-based educational materials 188,190 LGBTQ + -inclusive forms and decision-making tools 188,190 Physicians with disabilities Recruitment and workforce culture Include disability in discussions of diversity 4,191,192 Increase recruitment 193 Remove pressure on students and physicians to disclose the full nature of their disability 4 Improve and standardize medical school technical standards 194 addressing unclear, inconsistent, and lengthy policies and processes 4 Define responsibility for accommodations 4,194 Provide access to appropriate accommodations, personal and professional networks, peer support, and mentorship 4 Expand study of barriers and accommodations supportive of physicians [194][195][196] Patient comfort, communication, and outcomes Improve access, provider awareness, and communication, and address attitudinal barriers [45][46][47][48][49]195,[197][198][199] anxiety, low perceived self-health, harassment, and isolation. 130 Burnout in physicians with disabilities and intersectional identities Unfortunately, we were unable to find any study specifically aimed at examining burnout in physicians with disabilities or with intersectional identities, making these important areas for future research.…”
Section: Patient Comfort Communication and Outcomesmentioning
confidence: 99%
“…LGBTQ + -inclusive evidence-based educational materials 188,190 LGBTQ + -inclusive forms and decision-making tools 188,190 Physicians with disabilities Recruitment and workforce culture Include disability in discussions of diversity 4,191,192 Increase recruitment 193 Remove pressure on students and physicians to disclose the full nature of their disability 4 Improve and standardize medical school technical standards 194 addressing unclear, inconsistent, and lengthy policies and processes 4 Define responsibility for accommodations 4,194 Provide access to appropriate accommodations, personal and professional networks, peer support, and mentorship 4 Expand study of barriers and accommodations supportive of physicians [194][195][196] Patient comfort, communication, and outcomes Improve access, provider awareness, and communication, and address attitudinal barriers [45][46][47][48][49]195,[197][198][199] anxiety, low perceived self-health, harassment, and isolation. 130 Burnout in physicians with disabilities and intersectional identities Unfortunately, we were unable to find any study specifically aimed at examining burnout in physicians with disabilities or with intersectional identities, making these important areas for future research.…”
Section: Patient Comfort Communication and Outcomesmentioning
confidence: 99%
“…The population of DHoH individuals in medicine is heterogeneous in many ways, including variation in hearing acuity, communication styles and preferences, and accommodations used 4 . It is critical that admissions committees, faculty, and administrators do not make assumptions about which accommodations are needed for an individual DHoH student or physician.…”
Section: Ways To Better Support Dhoh Physicians and Physicians-in-tramentioning
confidence: 99%
“…Moreland and colleagues reported that DHoH respondents spent on average 1.3 hours per week to arrange for accommodations. 4 …”
Section: Ways To Better Support Dhoh Physicians and Physicians-in-tramentioning
confidence: 99%
See 1 more Smart Citation
“…2 This represents a larger cohort of students with disabilities entering GME than previously imagined [3][4][5] and suggests potential increases in requests for accommodation. Numerous resources exist to aid undergraduate medical education programs in disability-related recruitment and retention efforts, [6][7][8][9][10][11][12][13] including guidance on technical standards, 14,15 clinical accommodations, 16 and inclusive assessment. 17,18 The GME guidance is less robust.…”
mentioning
confidence: 99%